Browse's introduction to the symptoms and signs of surgical disease - Browse, Norman L. (Norman Leslie) (Hodder Education, 2005)
Giving an insight into the principles of surgery, this book presents the developments in this field. It pays attention to muscles, tendons, bones, joints and breast, and includes the classification of cancer staging. It contains illustrations and photographs showing the subtle surgical signs and demonstrating approaches to surgical examination.